Local Culture Integration in English Language Teaching Materials - Ni Nyoman Tantri (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The integration of culture in English Language Teaching (ELT) has become increasingly important as language is recognized as a social and cultural practice. In many EFL contexts, ELT materials are predominantly oriented toward Western cultures, which may create a cultural gap between learning content and learners’ lived experiences. This study aims to examine the integration of local culture in ELT materials and explore its pedagogical significance for EFL classrooms. Employing a qualitative descriptive research design, this study analyzed selected English teaching materials through document analysis, focusing on textual, visual, and task-based representations of local culture. The data were examined to identify forms of cultural representation, pedagogical functions, and the extent to which local culture supports meaningful language learning. The findings reveal that local culture is integrated through familiar themes such as traditions, daily social practices, and local values, which enhance learners’ comprehension, engagement, and confidence in using English. However, the integration remains limited and often superficial compared to the dominance of Western cultural content. The study concludes that local culture plays a crucial role in creating culturally responsive and contextually grounded ELT materials. A more systematic and balanced incorporation of local culture is therefore recommended to support effective language learning and intercultural competence in EFL contexts.